MARKETING DISTRIBUTION OF TILAPIA FISH (OREOCHROMIS NILOTICUS) IN BANJAR REGENCY OF SOUTH KALIMANTAN, INDONESIA - Lilimantik E.; Rahayu D. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
This study aims to examine the marketing channels and marketing agencies of tilapia fish in Banjar Regency, South Kalimantan. The data required were primary and secondary data. Primary data obtained through surveys, interviews with questionnaires to respondents and documentation. The primary data in this study were fish farmer and market agencies. Secondary data obtained from various sources and institutions related to the research description include books, magazines, journals and other official sources both from government and private agencies. The total respondents in this study were 74 people consisting of 45 fish farmers, using the simple random sampling method and then 9 middleman and 20 retailers using the snowball sampling method. The data analysis includes marketing agencies analysis and marketing channel analysis. The results of the analysis explain that there are two marketing agencies, namely middleman and retailers, and three patterns of marketing channels, namely (a) fish farmers directly sell to consumers, (b) fish farmers sell to middleman then sell to retailers for distribution to consumers and (c) fish farmers sell to retailers for distribution to consumers. Consumers as the final buyers come from the Regencies of Banjar, Banjarmasin, Banjarbaru, Tanah Laut, Hulu Sungai Utara, Hulu Sungai Selatan, and even out of South Kalimantan such as Central Kalimantan and East Kalimantan. The difference in the sales area illustrates that tilapia fish is starting to be in demand and already has a relatively wide market share.